Work Environment and Organizational Commitment of Librarians in Tertiary Institutions in Lagos State, Nigeria (Lead City International Journal of Library, Information & Communication Sciences, 2025)
This study examines the work environment and organizational commitment of librarians in tertiary institutions in Lagos State, Nigeria. Using a quantitative approach, it evaluates three dimensions of organizational commitment such as affective, continuance, and normative and also the four aspects of the work environment which include Cost/Rewards, Outcome Expectation, Equity/Fairness, and Reciprocity. Findings reveal low levels of affective and continuance commitment, both with a mean score of 2.47, reflecting limited emotional attachment and perceived costs of leaving the organization. Normative commitment recorded a higher mean score of 2.74, indicating that ethical obligations and loyalty are stronger drivers of commitment. The aggregate mean score of 2.56 indicates a moderate overall level of organizational commitment. In contrast, the work environment is assessed positively, with an aggregate mean score of 3.31. Outcome Expectation and Reciprocity dimensions scored the highest (3.38), highlighting positive perceptions of role significance and a collaborative culture. The Equity/Fairness dimension, with a mean score of 3.31, reflects fairness in treatment, promotion, and workload distribution. However, the Cost/Rewards dimension recorded the lowest mean score (3.17), indicating dissatisfaction with compensation and recognition. While the work environment in academic libraries in Lagos State is favorable, organizational commitment remains moderate, driven primarily by normative factors. Addressing deficiencies in compensation and recognition and fostering stronger emotional connections to the organization are recommended to enhance commitment and retention among librarians.